Applying XBRL, RegTech, and DLT to Strengthen Shareholders’ Rights in Uzbekistan - Habibullaev, Asliddin (Indonesian Scientific Publication, 2025)
Despite the rapid digital transformation taking place in Uzbekistan, the application of XBRL, RegTech, and DLT to the exercising of property and corporate shareholder rights has not yet been studied. Technologies such as XBRL, RegTech, and DLT offer potential to improve shareholders’ rights protection through process automation. This study explores how each of the above digital technologies can provide access to information, fulfil regulatory requirements and facilitate the transfer of ownership of shares. In this scientific article the following methods were used: legal-dogmatic and comparative-legal analysis, qualitative and quantitative analysis, analysis of positive and negative impact, as well as synthesis of results. The study found that: 1) with the help of XBRL, shareholders would have quick access to the information of the joint-stock company, which would help exercise the right to information; 2) with the help of RegTech, shareholders could timely stop wrongful related-party transactions and large transactions; 3) with the help of DLT, shareholders could quickly, transparently, and reliably realize the shares belonging to them. The results of the research show how the regulator of Uzbekistan can apply XBRL, RegTech, and DLT to the activities of joint-stock companies. The conclusion indicates that XBRL, RegTech, and DLT can be applied to the exercise of shareholders’ property and corporate rights, and proposals are given for the phased implementation of these digital technologies in a test mode.